구성원의 감사성향이 조직시민행동에 미치는 영향 : 조직지원인식과 직무만족의 다중매개효과를 중심으로 - 김창동; 오상진; Kim, Chang-Dong; Oh, Sang-Jin (한국콘텐츠학회 논문지, 20(4), 2020)
The purpose of this study is to find out how employee's gratitude disposition affects Organizational Citizenship Behavior(OCB) and empirically validating multiple mediation effect of perceived organizational support(POS) and job satisfaction. For this study, an online survey has been conducted on office workers to analyze 380 sets of answers, reviewed reliability and validity through CFA and used SPSS 25.0, AMOS 25.0, Macro Process 3.0, a bootstrap method to test hypothesis. As a result, it is verified that an employee's gratitude disposition positively affects OCB, POS and job satisfaction and that there exists a multiple mediation effect of POS and job satisfaction. In this study, it is validated that an employee's gratitude disposition has a positive influence on OCB and an employee's gratitude disposition, an individual trait, is a related antecedent variable of POS. The result of this study is meaningful that it suggests boosting gratitude disposition, a positive psychological factor, in an organization can positively affect employees' job attitude and organization effectiveness. 본 연구의 목적은 조직구성원의 감사성향이 조직시민행동에 어떠한 영향을 미치는지 알아보고, 그 관계에서 조직지원인식과 직무만족의 다중매개효과를 실증적으로 확인하는 데 있다. 이를 위해 사무직 근로자를 대상으로 온라인 설문 조사를 실시하여 380부를 분석하였으며, CFA를 통해 신뢰도 및 타당성을 검토하고, SPSS 25.0와 AMOS 25.0, 부트스트랩 방식의 Macro Process 3.0을 활용하여 가설검증 하였다. 검증 결과 조직구성원의 감사성향은 조직시민행동, 조직지원인식, 직무만족에 정(+)의 영향을 주었으며, 조직지원인식과 직무만족의 다중매개효과도 확인이 되었다. 조직구성원의 감사성향이 조직시민행동에 긍정적 영향을 준다는 것을 검증하였고, 구성원 개인특성인 감사성향이 조직지원인식의 유의한 선행변인이라는 점을 확인하였다. 본 연구결과를 통해 조직에서 긍정심리 요소인 감사성향을 증진하는 것이 구성원 직무 태도 및 조직효과성에 긍정적인 영향을 줄 수 있다는 가능성을 제시했다는 점에서 의미가 있다.